Fetal Aortic Valvuloplasty for Evolving Hypoplastic Left Heart Syndrome: A Decision Analysis - Pickard, Sarah S. (Circ Cardiovasc Qual Outcomes, 2020)
BACKGROUND: Fetal aortic valvuloplasty (FAV) may prevent progression of mid-gestation aortic stenosis (AS) to hypoplastic left heart syndrome (HLHS). However, FAV has well-established risks, and its survival benefit remains unknown. Our primary aim was to determine if FAV for mid-gestation AS increases survival from fetal diagnosis to age 6. METHODS AND RESULTS: We performed a retrospective analysis of 143 fetuses who underwent FAV from 2000-2017 and a secondary analysis of the Pediatric Heart Network Single Ventricle Reconstruction trial. Using these results, we developed a decision model to estimate probability of transplant-free survival from fetal diagnosis to age 6 and postnatal restricted mean transplant-free survival time (RMST). FAV was technically successful in 84% of 143 fetuses with fetal demise in 8%. Biventricular circulation was achieved in 50% of 111 liveborn infants with successful FAV but in only 16% of the 19 patients with unsuccessful FAV. The model projected overlapping probabilities of transplant-free survival to age 6 at 75% (95% CI 67% - 82%) with FAV versus 72% (95% CI 61% - 82%) with expectant fetal management, resulting in a RMST benefit of 1.2 months. When limiting analyses to the improved FAV experience since 2009 to reflect current practice, probability of technical success (94%), fetal demise (4%), and biventricular circulation (66%), the model projected that FAV increased the probability of survival to age 6 to 82% (95% CI 73% - 89%). Expectant management is favored if risk of fetal demise exceeded 12% or probability of biventricular circulation fell below 26%, but FAV remained favored over plausible recent range of technical success. CONCLUSIONS: Our model suggests that FAV provides a modest, medium-term survival benefit over expectant fetal management. Appropriate patient selection and low risk of fetal demise with FAV are critical factors for obtaining a survival benefit.